К ЮБИЛЕЮ ПРОФЕССОРА ГУЗЕВОЙ ВАЛЕНТИНЫ ИВАНОВНЫ - Оксана Валентиновна Гузева; Виктория Валентиновна Гузева; Михаил Анатольевич Разумовский; Инна Владимировна Охрим (Children's Medicine of the North-West, 2024)
К ЮБИЛЕЮ ПРОФЕССОРА ГУЗЕВОЙ ВАЛЕНТИНЫ ИВАНОВНЫ